Tourism ventures and their contribution to the economic growth of the city of Manta - Lucas Mantuano, Carmen Auxiliadora (Scripta Mundi, 2024)
The article presented below titled “Tourism Entrepreneurship and its contribution to the Economic Growth of the city of Manta, is a research that aims to analyze how tourism ventures contribute to the economic development of the city. Knowing that tourism has emerged as one of the most dynamic and fastest growing industries in the world, generating significant opportunities for the economic development of various regions, where the city of Manta stands out for its tourism potential, thanks to its beaches, its rich culture and gastronomy. The methodological approach used was quantitative and qualitative, offering a comprehensive vision of the current situation of tourism in Manta. As results of the research, it was obtained that the tourism sector maintains important income in the city’s businesses. At the end of the work it is concluded that the contribution of tourism ventures to the economic growth of the city of Manta is very significant.